The effect of salsola tuberculatiformis bostchantzev on the androgen and glucocorticoid receptors in prostate cancer cell lines - Kelbe, Lisa Suzanne (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.